A note on dynamic hedging: Empirical evidence from FTSE-100 and S&P 500 futures markets. Issue 2 (16th March 2015) - Alghalith, Moawia; Floros, Christos; Lalloo, Ricardo
Abstract : Purpose: – The purpose of this paper is to empirically test dynamic hedging, using data from the FTSE-100 and Standard & Poor's (S&P) 500 futures indices. Design/methodology/approach: – The authors introduce a dynamic continuous-time hedging model in futures markets. The authors further relax the statistical-independence assumption between the spot price and basis risk. Findings: – The authors show that the investors are, on average, quite risk averse. The authors find that a one unit increase in the price volatility reduces the hedged FTSE-100 (S&P 500) by 645.62 (777.07) units. Similarly, a one unit increase in basis risk reduces the hedged FTSE-100 (S&P 500) by 403.57 (378.54) units. The authors' approach shows that risk-averse investors should decrease their hedge (i.e. increase their equity allocation) with an increase in index price risk. Practical implications: – These findings are helpful to risk managers dealing with futures markets. Originality/value: – The contribution of this paper is that it successfully introduces a dynamic continuous-time hedging model in futures markets.